2004
DOI: 10.1094/pdis.2004.88.6.645
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fusarium oxysporum Isolates Obtained from Cucumber in China by Pathogenicity, VCG, and RAPD

Abstract: Thirty-four isolates of Fusarium oxysporum, obtained in China from cucumber plants showing either Fusarium wilt (F. oxysporum f. sp. cucumerinum) or root and stem rot (F. oxysporum f. sp. radicis-cucumerinum) symptoms, were characterized by pathogenicity, vegetative compatibility, and random amplified polymorphic DNA (RAPD). Of these, 23 isolates were identified by pathogenicity as F. oxysporum f. sp. cucumerinum, and one as F. oxysporum f. sp. radicis-cucumerinum, while 10 isolates were avirulent on cucumber,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…apii isolates was found to be correlated with VCG. Vakalounakis et al (2004) and Ahn et al (1998) also found out that the virulence of F. oxysporum f.sp. cucumerinum in China and Korea was associated with VCG.…”
Section: Pathogenicity and Aggressiveness Of F Oxysporum Isolates Onmentioning
confidence: 90%
“…apii isolates was found to be correlated with VCG. Vakalounakis et al (2004) and Ahn et al (1998) also found out that the virulence of F. oxysporum f.sp. cucumerinum in China and Korea was associated with VCG.…”
Section: Pathogenicity and Aggressiveness Of F Oxysporum Isolates Onmentioning
confidence: 90%
“…Final observations on disease development were made 14 days after inoculation as described by Vakalounakis et al (2004) Eight replicate pots of each treatment were used. Tests were repeated once.…”
Section: Harvest and Chemical Analysismentioning
confidence: 99%
“…Concerning vegetative compatibility in Verticillium dahliae, Rataj-Guranowska et al (2016) observed bridges between American testers VCG 2 and VCG 4, also between American and Dutch testers and between subgroup testers VCG 2A and 2B. The occurrence of these bridging strains is well known in F. oxysporum (Vakalounakis and Fragkiadakis 2004). Another difference between FOP and other formae speciales is demonstrated by the anomalies found in the pairings of race 1 isolates.…”
Section: Discussionmentioning
confidence: 91%
“…However, isolates belonging to different VCGs can also belong to the same clonal lineage (Baayen et al 2000). Several formae speciales of F. oxysporum have been characterized by VCG analysis (Lori et al 2004;Abo et al 2005), as well as by random amplified polymorphio DNA (RAPD) analysis (Alves-Santos et al 2007;Bayraktar et al 2008;Baysal et al 2010) and several studies have combined both markers (Vakalounakis et al 2004;Nagarajan et al 2006). This technique is appropriate for developing countries with inadequate facilities for molecular work and can rapidly determine genetic groups of many fungal pathogens and their relation to pathogenicity (Cumagun et al 2008).…”
Section: Introductionmentioning
confidence: 99%